Threat modelling with UML for cybersecurity risk management in OT-IT integrated infrastructures - Sharif, Ali (My University, 2022)
A strong cybersecurity threat management can provide a good security situation against malicious attacks designed to access, modify, delete, destroy or capture user or organization systems and sensitive data. In this work, first the issue of cybersecurity is described, then the common attacks of OT-IT integrated systems as target systems are examined. The concentration area of this thesis is about the security of OT-IT systems. The purpose of this thesis is to provide a Cybersecurity risk management solution fundamentally focused on detecting common cybersecurity intrusions which are widely being used by the malicious attacks to forcefully abuse or take advantage of preciously a computer network. The main idea of this project is to providing a solution which can help the cybersecurity experts of OT-IT companies to catch the abnormalities of the network practically by the time a pre-defined intrusion is being executed by an attacker, in order to give more defensive power against the possible threats. In chapter 3 There will be proposed model is designed with UML and SysML in Eclipse Papyrus software which is a great tool to model a system. Here, I presented a threat modeling detection system which is practically an IDS. Finally, the model will be implemented using the PCA methods and the SVM, which are part of machine learning techniques. The Intrusion Detection System is implemented and the results show the high efficiency of the proposed method.
Keywords: Cyber security, Intrusion detection system, UML, SysML, Support vector machine, principal component analysis, OT-IT